Pengaruh Penilaian Risiko dan Perlakuan Risiko Terhadap Penerapan Manajemen Risiko dengan Unit Manajemen Risiko Sebagai Pemoderasi (Studi Pada PT Permodalan Nasional Madani Venture Capital) - Sarni, Neng; Prowanta, Embun (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
The aims to analyze the influence of risk assessment and risk treatment on the implementation of risk management at PT Permodalan Nasional Madani Venture Capital, with the risk management unit as moderator. Risk assessment and risk treatment are two crucial components in effective risk management, especially in the context of non-bank financial institutions such as PT Permodalan Nasional Madani Venture Capital. This research uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to employees involved in the company's business processes. The research results show that risk assessment and risk treatment significantly influence the implementation of risk management. In addition, the risk management unit is proven to moderate the relationship between risk assessment and risk management implementation, as well as between risk treatment and risk management implementation. These findings emphasize the important role of the risk management unit in strengthening the effectiveness of risk assessment and treatment in the implementation of overall risk management in the company. Keywords: Risk Assessment, Risk Treatment, Risk Management, Risk Management Unit.